Expression and immunolocalization of the multidrug resistance proteins, MRP1-MRP6 (ABCC1-ABCC6), in human brain - Nies, Andrea; Jedlitschky, Gabriele; Herold-Mende, Christel; Steiner, Hans H.; Schmitt, Horst Peter (Neuroscience, 2004)
Multidrug resistance proteins (MRPs, symbol ABCC) are membrane glycoproteins that mediate the ATP-dependent export of organic anions, including cytotoxic and antiviral drugs, from cells. To identify MRP family members possibly involved in the intrinsic resistance of human brain to cytotoxic and antiviral drugs, we analyzed the expression and localization of MRP1-MRP6 in rapidly frozen perilesional samples of several regions of adult human brain obtained during neurosurgery. Quantitative polymerase chain reaction analysisshowed expression of MRP1, MRP2, MRP3, MRP4, and MRP5 mRNA, whereas MRP6 mRNA was below detectability. However, immunofluorescence microscopy of cryosections from human brain showed no reactivity for the MRP2 or MRP3 proteins. The proteins MRP1, MRP4, and MRP5 were clearly localized by confocal laser scanning microscopy to the luminal side of brain capillary endothelial cells. The MRP4 and MRP5 proteins were also detected in astrocytes of the subcortical white matter. Notably, MRP5 protein was present in pyramidal neurons. MRP proteins may, thus, contribute to the cellular efflux of endogenous anionic glutathione or glucuronate conjugates (substrates for MRP1), cyclic nucleotides (substrates for MRP4 and MRP5), or glutathione (co-substrate for MRP1 and MRP4); in addition, they may play an important role in the resistance of the brain to several cytotoxic and antiviral drugs.